Comparative Study of Education Systems: A Focus on Indonesia and Countries Across Asia and Australia - Rahmawati, Rafika; Hendra Saputra, Arsyil; R Madhakomala (Siber International Journal of Digital Business (SIJDB), 2024)
This study aims to conduct a comparative analysis of the education systems in Indonesia and other countries across Asia and Australia. The countries included in this comparison are Japan, China, South Korea, Vietnam, and Australia. The objective is to identify best practices and challenges that Indonesia faces in improving its educational quality and global competitiveness. A qualitative library research method was employed, involving an extensive review of literature, including academic journals, research reports, and official documents, to gather comprehensive data on various aspects of each education system, such as curriculum structure, assessment methods, technology integration, and educational philosophies. The results indicate significant differences in educational approaches, with Indonesia's centralized curriculum focusing on uniformity and cultural values, while other countries emphasize flexibility, innovation, and technology-driven practices. Strategic recommendations are provided to improve Indonesia's education system, ensuring it meets local needs while remaining competitive on a global scale. This analysis serves as a valuable resource for policymakers, educators, and stakeholders aiming to enhance educational outcomes.